On the unintended consequences of online teaching: A response - Waghid, Y. (South African Journal of Higher Education, 2021)
This article is a response to claims that online education is a pedagogical risk for teaching-learning. Of course, notions of privacy, authenticity, and ownership are real challenges to higher education but these complexities do not have to subvert engaged teaching-learning at higher education institutions. I offer a brief response as to why teaching-learning as a deliberative encounter does not have to be sacrificed with-in online education.